SELEKSI SAHAM SYARIAH : PERBANDINGAN ANTARA BURSA EFEK INDONESIA DAN MALAYSIA - Egi Arvian Firmansyah (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2017)
Abstract. Islamic stocks are those which do not contradict with the Islamic teachings derived from Al-Quran, Sunnah, hadith and ijtihad of the qualified Islamic scholars. This is a qualitative research comparing the stock screening criteria in order to be categorized as sharia compliant stocks in two developing countries where most of the citizen are Muslims, i.e. Indonesia and Malaysia. As the sharia stock screening is in the field of muamalah and there is no single scholar (or group) accepted by the whole Muslims worldwide, each country sets its own screening criteria through its Islamic scholars by performing ijtihad as an effort to decide the sharia compliant stocks. It was found that there are differences in screening criteria between Indonesia and Malaysia stock exchange. These are based on the fiqh or understanding of the scholars in the two countries as well as the vision and investor to be targeted. The screening criteria need to be continuously improved or revised along with the changing need of investor and stock exchange strategy in collecting the fund especially from Middle East countries requiring sharia compliance.Keywords. ISSI; JII; stock screening; sharia stock selection. Abstrak. Saham Syariah merupakan saham yang tidak bertentangan dengan ajaran Islam yaitu yang bersumber dari Al-Quran, Sunnah, hadist dan ijtihad ulama terkemuka. Penelitian ini merupakan penelitian kualitatif yang membandingkan kriteria seleksi saham untuk dapat dikategorikan ke dalam saham syariah di dua negara berkembang yang penduduknya mayoritas Muslim yaitu Indonesia dan Malaysia. Karena skrining saham syariah termasuk ke dalam aspek muamalah dan tidak adanya ulama yang diterima oleh umat Muslim seluruh dunia untuk menentukan satu hukum yang diterima umum, maka setiap negara dengan ulamanya masing-masing menggunakan pendekatan ijtihad untuk memutuskan saham mana yang dikategorikan sesuai syariah dan tidak. Terdapat perbedaan kriteria seleksi di Indonesia dan Malaysia yang didasarkan pada pemahaman fiqih yang dianut masing-masing negara serta visi dan target investor yang ingin diraih. Metode skrining senantiasa perlu dievaluasi atau direvisi seiring perubahan selera investor dan strategi bursa dalam mengumpulkan dana terutama dari negara-negara Timur Tengah yang memperhatikan aspek kepatuhan pada syariah.Katakunci. ISSI; JII; stock screening; seleksi saham syariah.